e-Module Design with Content Based Instruction in Reading for Academic Purpose - Nurul Aini; Eny Maulita Purnama Sari; Willy Artanika Rikarda (Ilmu Pendidikan: Jurnal Kajian Teori dan Praktik Kependidikan, 2020)
Abstract: This research emphasizes on e-Module based on content-based instruction (CBI) in Reading for Academic Purpose subject. This design implements the Islamic values of rahmatanlil’alamin. Students and lecturers of English Education Study Program do not have and never received an e-module for reading subject that involved Islamic values and digital content according to their background and is compatible with e-Learning that has been running University that is UNUSmartDaring. The aims of this study are to design an e-Module based Content Based Instruction (CBI) and measure its success in reading mastery of the fourth semester students of English Education. This e-Module design was created in order to improve the mastery of pedagogic concepts and the competence of English Education students as prospective teachers. To produce the expected product, researchers used the Analysis, Design, Development, Implementation, Evaluation (ADDIE) method. The activity of preparing the e-Module based Content Based Instruction (CBI) Design in the Reading for Academic Purpose Course to determine the effectiveness of using module in the English Education Study Program is carried out in three stages, namely: (1) Preliminary Study, including the study of reading theory for academic purposes, Content Based Instruction (CBI) theory, as well as UNUSmartDaring software; (2) designing module, compiling module assessment instrument, compiling the evaluation instrument; and (3) Product Testing stage, module review by experts, small-scale trials, online use trials, classroom use, evaluation and module based Content Based Instruction (CBI) for teaching Reading. The average value obtained was 41.4 with good category based on the result of validation analysis.